Minimizing roadway embankment damage from flooding - Briaud, J.-L; Maddah, Layal (Transportation Research Board, 2016)
This state-of-the-practice report highlights how the transportation community is protecting roadways and mitigating damage from inundation and overtopping. In the absence of standard guidance, this report highlights major issues and design components specific to roadway embankment damage from flooding. It documents the mechanics of damage to the embankment and pavement, and the analysis tools available. The probable failure mechanisms are identified and various design approaches and repair countermeasures are highlighted. The information presented in the synthesis is based on a review of the related literature, a survey of current practice, and a series of telephone interviews with state departments of transportation. Examples of failures and repair techniques are illustrated through 14 case examples gathered from six states. The findings suggest that minimizing damage to roadway embankments can be tackled by altering the embankment design and slope protection techniques or altering the stream course, or both. The success of an approach is site-dependent because an approach that serves its intended design purpose at one site does not necessarily work at another site. To arrive at an adequate design, the following factors should be considered: hydrologic and hydraulic factors, geological and geotechnical factors, legal and funding aspects, and risk. Ideally, it is the combination of the probability of failure and the value of the consequence or risk that can most effectively guide the decision.
Keywords: Roads -- Embankments -- Protection.; Flood damage prevention.; Roadside improvement.; elektronické knihy; electronic books